Learning the Kitab 'Uqu̅dullujain with the Zoom Application - Afifah, Dewi; Mashudi; Fathiyaturrahmah (Journal of Islamic Education, 2024)
The high divorce rate in East Java, especially in Jember, requires a study of science that can mitigate divorce in the household. This research, which was carried out at the Al-Khozini Student Dormitory, aims to determine the objectives, materials, methods and media used in studying the book 'Uqu̅dullujain using the Zoom application among students in Kaliwates Jember. This article uses a qualitative research approach with a case study type of research. The collection technique uses structured interviews, non-participatory observation, and documentation. There are two types of data validity in this research, namely source triangulation and technical triangulation. Data analysis in the research used the Milles and Huberman model. 'Uqu̅dullujain's research learning with Zoom at the Al-Khozini Kaliwates School in Jember revealed harmony with Islamic boarding school regulations, emphasis on marital obligations. Overall, this research highlights effective methods and media for conveying important knowledge about marital responsibilities. These findings reflect Hamzah B. Uno's cognitive domain theory for establishing goals and Reigeluth's categorization for cognitive material. The method (bandongan and lecture) is in line with Akhiruddin and Zainal Aqib's theory, while the use of media (books, notes, Zoom) is in accordance with Hujair AH Sanaky's classification.